The SARS‐unique domain (SUD) of SARS‐CoV and SARS‐CoV‐2 interacts with human Paip1 to enhance viral RNA translation. (20th April 2021) - Lei, Jian; Ma‐Lauer, Yue; Han, Yinze; Thoms, Matthias; Buschauer, Robert; Jores, Joerg; Thiel, Volker; Beckmann, Roland; Deng, Wen; Leonhardt, Heinrich; Hilgenfeld, Rolf; von Brunn, Albrecht
Abstract: The ongoing outbreak of severe acute respiratory syndrome (SARS) coronavirus 2 (SARS‐CoV‐2) demonstrates the continuous threat of emerging coronaviruses (CoVs) to public health. SARS‐CoV‐2 and SARS‐CoV share an otherwise non‐conserved part of non‐structural protein 3 (Nsp3), therefore named as "SARS‐unique domain" (SUD). We previously found a yeast‐2‐hybrid screen interaction of the SARS‐CoV SUD with human poly(A)‐binding protein (PABP)‐interacting protein 1 (Paip1), a stimulator of protein translation. Here, we validate SARS‐CoV SUD:Paip1 interaction by size‐exclusion chromatography, split‐yellow fluorescent protein, and co‐immunoprecipitation assays, and confirm such interaction also between the corresponding domain of SARS‐CoV‐2 and Paip1. The three‐dimensional structure of the N‐terminal domain of SARS‐CoV SUD ("macrodomain II", Mac2) in complex with the middle domain of Paip1, determined by X‐ray crystallography and small‐angle X‐ray scattering, provides insights into the structural determinants of the complex formation. In cellulo, SUD enhances synthesis of viral but not host proteins via binding to Paip1 in pBAC‐SARS‐CoV replicon‐transfected cells. We propose a possible mechanism for stimulation of viral translation by the SUD of SARS‐CoV and SARS‐CoV‐2. SYNOPSIS: The presence of a "SARS‐unique domain" (SUD) in non‐structural protein 3 (Nsp3) of SARS‐CoV and SARS‐CoV‐2 offers an opportunity to study its specific modulation of host cells. Here, biochemical and structural data demonstrate SUD interaction with host translation factor Paip1, and its effect on viral protein synthesis in human cells. The SUD of SARS‐CoV and SARS‐CoV‐2, but not of MERS‐CoV, interacts with human Paip1 (PABP‐interacting protein) in vitro and in cells. X‐ray crystal structure and SAXS data define the interaction between Paip1 and macrodomain II (Mac2) in the SARS‐CoV SUD. The SUD forms a ternary complex with Paip1 and PABP and interacts with 40S/80S ribosomal particles in cells. The Nsp3 SUD enhances viral but not host protein synthesis in SARS‐CoV replicon‐transfected cells via the SUD:Paip1 interaction. Abstract : Structural and functional analysis of the association of the Nsp3 SUD domain with the host translation regulator Paip1 reveals its role in promoting viral but not host protein synthesis in SARS‐CoV‐infected cells.